Not All Trees Sleep the Same—High Temporal Resolution Terrestrial Laser Scanning Shows Differences in Nocturnal Plant Movement - Zlinszky, András; Molnár, Bence; Barfod, Anders S. (Frontiers in Plant Science, 2017)
Circadian leaf movements are widely known in plants, but nocturnal movement of tree branches were only recently discovered by using terrestrial laser scanning, a high resolution three-dimensional surveying technique. Terrestrial laser scanning uses a pulsed laser emitted in a regular scan pattern for rapid measurement of distances to the targets, thus producing three dimensional point cloud models of sub-centimeter resolution and accuracy in a few minutes. Here we aim to gain an overview of the variability of circadian movement of small trees across different taxonomic groups, growth forms and leaf anatomies. We surveyed a series of 18 full scans over a 12-hour night period to measure nocturnal changes in shape simultaneously for an experimental setup of 22 plants representing different species. Resulting point clouds were evaluated by comparing changes in height percentiles of laser scanning points belonging to the canopy. Changes in crown shape were observed for all studied trees, but clearly distinguishable sleep movements are apparently rare. Ambient light conditions were continuously dark between sunset (7:30 PM) and sunrise (6:00 AM), but most changes in movement direction occurred during this period, thus most of the recorded changes in crown shape were probably not controlled by ambient light. The highest movement amplitudes,for periodic circadian movement around 2 cm were observed for Aesculus and Acer, compared to non-periodic continuous change in shape of 5 cm for Gleditschia and 2 cm for Fargesia. In several species we detected 2-4 hours cycles of minor crown movement of 0.5-1 cm, which is close to the limit of our measurement accuracy. We present a conceptual framework for interpreting observed changes as a combination of circadian rhythm with a period close to 12 hours, short-term oscillation repeated every 2-4 hours, aperiodic continuous movement in one direction and measurement noise which we assume to be random. Observed movement patterns are interpreted within this framework, and connections with morphology and taxonomy are proposed. We confirm the existence of overnight “sleep” movement for some trees, but conclude that circadian movement is a variable phenomenon in plants, probably controlled by a complex combination of anatomical, physiological and morphological factors.